2015
DOI: 10.1016/j.ijhydene.2014.10.111
|View full text |Cite
|
Sign up to set email alerts
|

On the tortuosity factor of solid phase in solid oxide fuel cell electrodes

Abstract: Tortuosity factor τ of the solid phase is an important parameter for the accurate prediction of SOFC electrode conductivity. This work investigates the effect of computational domain on τ. The results show that a computational domain with cross section area of 15d*15d (d: particle diameter) is necessary for the calculation of τ when 15% deviation is allowed. The result also validates that the anisotropic property of τ shown in the previous literatures is caused by the insufficient sample size. This study build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
(40 reference statements)
0
22
0
Order By: Relevance
“…7. An allowed deviation of 15 % is chosen for all the parameters in this study to be defined as stable status [14]. It is seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7. An allowed deviation of 15 % is chosen for all the parameters in this study to be defined as stable status [14]. It is seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have investigated the influence of 3D reconstruction size on the statistic quantitative information of composite cermet microstructure [12][13][14][15]. The maximum size of 3D reconstruction based on FIB-SEM technique was limited by SEM image drifting and shadow effects which is quite difficult to be solved in the current stage.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the voxel length (L vox ) in computational domain is unfixed while the particle radius (r) is set as 10 times of the voxel length (i.e., r=10L vox ) to ensure the model accuracy (7). Therefore, by expanding the particles along the particle radius by a factor of 1.1 (1 L vox ), contact angles of around 34 o can be generated between neighboring electrode particles (13). Different contact angles can be formed by dilating electrode particles with different factors.…”
Section: (A)mentioning
confidence: 99%
“…Costamagna et al [36] developed a microscopic model of an electrode formed by nearly spherical electronic and ionic conducting particles (i.e., randomly packed sphere theory). This modeling approach had also been used in recent studies [37,38]. The results showed that volumetric composition and particle size strongly influence power output.…”
Section: Introductionmentioning
confidence: 99%